Las afinidades plásticas de Islas (1958-1968) / Islas plastic affinities (1958-1968) (Islas, 2021)
En este artículo se valora la revista Islas (1958-1968) en sudiscurso interno bajo las pautas editoriales de Samuel Feijóo, cuandodeviene un órgano de difusión de textos e imágenes de las artes visualesregionales, cubanas y foráneas que la hacen merecedora de ser estimadaen su real dimensión en la historia del arte en Cuba. Los métodoshistórico-lógico, el histórico-crítico y el análisis documental, permitenun acercamiento a la importancia de la revista desde esa perspectiva.The internal discourse in Islas Magazine (1958-1968) is analyzedunder Feijoo’s editorial norms since it has turn into a publicationfor disseminating texts and images of the regional, Cuban and foreignvisual arts, that make Islas be esteemed in its full dimension in Cuban arthistory. The use of the historical-logical and the historical-critical methodsas well as documentary analysis allow an approach to the significanceof the magazine in that perspective.